Contribution of the Tourism Sector to Regional Original Income (PAD) Meta Analysis - Rahmatulloh, Nanda Alifuddin; Rasyid, Mohtar (Jurnal Ragam Pengabdian, 2026)
This study employs a meta-analysis approach to examine the influence of the tourism sector, particularly hotel occupancy rates, on Regional Original Income (PAD). The research applies a Systematic Literature Review (SLR) using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Literature searches were conducted through the GARUDA and Google Scholar platforms using the keywords “tourism” and “PAD” within the last eight years. A total of 140 articles were initially identified, followed by an inclusion and exclusion screening process that resulted in 19 eligible studies for analysis. The meta-analysis findings indicate that hotel occupancy rates have a positive and significant effect on PAD, with a combined effect size of 0.333, a 95% confidence interval ranging from 0.068 to 0.597, and a p-value of 0.0139. The analysis used a random effects model with the Restricted Maximum Likelihood (REML) method. Heterogeneity testing showed an I² value of 98.67%, indicating substantial variation among studies. Meta-regression analysis using moderator variables such as year, sample, panel, and journal revealed no significant moderating effects. However, subgroup analysis indicated differences in effect sizes across study groups. Overall, tourism contributes positively to increasing PAD.